Late bloomer ebook A novel. - Eddings, Mazey (St. Martin's Griffin, 2024)
A sexy, sapphic, opposites-attract romance with Mazey Eddings' signature sparkling voice! Winning the lottery has ruined Opal Devlin's life. After quitting her dead-end job where she'd earned minimum wage and even less respect, she's bombarded by people knocking at her door for a handout the second they found out her bank account was overflowing with cash. And Opal can't seem to stop saying yes. With her tender heart thoroughly abused, Opal decides to protect herself by any means necessary, which to her translates to putting almost all her new money to buying a failing flower farm in Asheville, North Carolina to let the flowers live out their plant destiny while she uses the cabin on the property to start her painting business. But her plans for isolation and self-preservation go hopelessly awry when an angry (albeit gorgeous) Pepper Boden is waiting for her at her new farm. Pepper states she's the rightful owner of Thistle and Bloom Farms, and isn't moving out. The unlikely pair strike up an agreement of co-habitation, and butt heads at every turn. Can these opposites both live out their dreams and plant roots? Or will their combustible arguing (and growing attraction) burn the whole place down?